Using open software application packages for simulation of viscous incompressible fluid - Shudrik, Aleksandr Leonidovich (НТУ "ХПИ", 2016)
This paper analyzes the basic principles, advantages and disadvantages of an open package OpenFOAM. Class hydrodynamics tasks are listed. Possibilities and prospects of further use of OpenFOAM accessible using a number of turbulence models in the study of the working process in hydraulic machines are shown. The calculations of test tasks of turbulent flow of viscous fluid in Newton's channels of variable section, the sudden expansion in the impeller vane pump. Results in the form of pressure fields (velocities), the integral defined by their characteristics are presented. An experiment on the stand of the Department "Hydraulic Machines". The comparison of results obtained in packages OpenFOAM, ANSYS CFX and experiments.

В работе проанализированы основные принципы, преимущества и недостатки работы с открытым пакетом OpenFOAM. Перечислен класс задач гидродинамики, возможности и перспектива дальнейшего использовании OpenFOAM при исследовании рабочего процесса в гидромашинах. Проведены расчеты тестовых задач турбулентного течения вязкой ньютоновской жидкости в каналах переменного сечения, внезапного расширения и в рабочем колесе лопастного насоса. Результаты расчетов представлены в виде полей давлений (скоростей), определены их интегральные характеристики. Приведено сравнение результатов, полученных в пакетах OpenFOAM, ANSYS CFX и экспериментах.
Использование открытых пакетов прикладных программ при моделировании течений вязкой несжимаемой жидкости
Keywords: computational fluid dynamics; turbulence model; mathematical model; mesh; OpenFOAM; вычислительная гидродинамика; модели турбулентности; математическая модель